Superbunching and nonclassicality as new hallmarks of superradiance - Bhatti, Daniel; von Zanthier, Joachim; Agarwal, Girish S. (Optics InfoBase Conference Papers, 2017)
We investigate the quantum statistical properties of superradiance by calculating the photon-photon correlations of doubly excited W-states. Our results show that nonclassical, bunched, and superbunched light can be emitted from systems in such states.
CRIS-Team Scopus Importer:2023-03-27